DETERMINAN PERILAKU STREET-LEVEL BUREAUCRATIC DALAM MENGIMPLEMENTASIKAN PROGRAM PUBLIK : (Studi Kasus pada Program Desa Cinta Statistik (Cantik) BPS Tahun 2022) - Roudhotul Jannah (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Determinans of Public Program Implementation Street-level Bureaucratic’s Behavior (Case Study of the 2022 BPS Desa Cantik Program). One of the Central Statistics Agency (BPS)’s functions which is spelled out in Law Number 16 of 1997 concerning Statistics and Presidential Regulation Number 39 of 2019 concerning One Indonesian Data is statistical data builder. To implement it, BPS has launched the Desa Cantik (Cinta Statistics) Program. This is a program for developing sectoral statistics at the village government level. The most dominant role in implementation is the village coach. Research was conducted to analyze the factors that influence the village coach to implement it. The sample was selected by using Systematic random sampling method and data were analyzed with the Generalized Structural Equation Model (GSEM). The research results are: (1) the level of Adoption, Fidelity and Effectiveness of village coach is 79.48 percent (2) program design, collaboration, management and target program’s response have positive effect to implementation behavior of village coach. (3) management is the variable that contributes the most to the village coach’s implementation behavior, program design makes the least contribution, while collaboration and target program’s response give almost the same effect. It can be concluded that the village coach’s implementation behavior still need to be improved by maximizing determinants that influence them